DESAIN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM BERBASIS EVOLUSI BUDAYA - Ulum, Itah Miftahul (Jurnal Pendidikan Agama Islam, 2016)
Purpose of this study was to determine relationship of al-Quran and al-Sunnah with the rules of fqh al-’ādatu muhakkamah and applicability in Islamic Religious Education (PAI) in Public Higher Education (PTU), with no “scrape” exhausted culture or on the contrary, so intertwined harmony between Muslims and adherents of culture in society. Method used in study is content analysis, which is used to understand the rules of Arabic in verses of the Koran and Hadith of the Prophet of Islam and culture. In addition, also used discourse analysis, which is to connect the to the context as meaning implied relating to circumstances at time of verses of Koran and Hadith of Prophet lowered. Results obtained from study of literature, that Islam gives the option to mankind to determine other options, recognize and protect the right to life adherents of a different culture, and Islam is a universal religion that has characteristics of al-wāqi’iyah (realistic), and can cooperate in preventing damage and build community. Keywords: Islamic religion and culture, al-’ādathu muhakkamah, Islamic Religious Education.